ChemInform Abstract: Crystal Growth and Characterization of the Narrow‐Band‐Gap Semiconductors OsPn2 (Pn: P, As, Sb). Issue 45 (23rd October 2014) - Bugaris, Daniel E.; Malliakas, Christos D.; Shoemaker, Daniel P.; Do, Dat T.; Chung, Duck Young; Mahanti, Subhendra D.; Kanatzidis, Mercouri G.
Abstract Single crystals of the title compounds are prepared from mixtures of Os, P or As, and Sn (1050 °C, 24 h), or Os and Sb (1150 °C, 48 h).